ANALISIS SUKU BUNGA, INFLASI DAN KREDIT MACET MODAL KERJA DI INDONESIA - Poeja Maura; Yeniwati Yeniwati (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to determine the effect of reference interest rates on inflation and bad credit working capital and also see how the effect of inflation on bad credit working capital in Indonesia. The type of research used is descriptive and associative research, namely research that describes the research variable and finds the presence or absence of influence between the independent variable and the dependent variable. The type of data in this study are quantitative secondary data and time series from 2016M6-2018M11 with documentation data collection techniques sourced from Bank Indonesia (BI), Financial Services Authority (OJK), Central Statistics Agency (BPS), and other library studies . Data were analyzed using multiple linear regression models with steps: (1) classical assumptions, (2) hypothesis testing, and (3) test coefficient of determination (R2). The results of this study indicate that: (1) The benchmark interest rate has a negative and significant relationship to inflation. (2) The reference interest rate has a positive and significant relationship to non-performing loans of working capital in Indonesia. (3) Inflation has a non-significant and negative relationship to non-performing loans of working capital in Indonesia. This study aims to determine the effect of reference interest rates on inflation and bad credit working capital and also see how the effect of inflation on bad credit working capital in Indonesia. The type of research used is descriptive and associative research, namely research that describes the research variable and finds the presence or absence of influence between the independent variable and the dependent variable. The type of data in this study are quantitative secondary data and time series from 2016M6-2018M11 with documentation data collection techniques sourced from Bank Indonesia (BI), Financial Services Authority (OJK), Central Statistics Agency (BPS), and other library studies . Data were analyzed using multiple linear regression models with steps: (1) classical assumptions, (2) hypothesis testing, and (3) test coefficient of determination (R2). The results of this study indicate that: (1) The benchmark interest rate has a negative and significant relationship to inflation. (2) The reference interest rate has a positive and significant relationship to non-performing loans of working capital in Indonesia. (3) Inflation has a non-significant and negative relationship to non-performing loans of working capital in Indonesia. <w:LsdException Locked="false" Priority="40" Name="Grid